Monitoring the effects of vehicle components' size on optimum structural crashworthiness. Issue 7 (3rd July 2021) - Ofochebe, Sunday Madubueze; Ozoegwu, Chigbogu Godwin
Abstract : To determine the effects of vehicle components' size on the optimum structural crashworthiness of a vehicle, sufficient data on the expected crash behaviour are required. Considering the high fiscal cost of obtaining the real crash test data, and extreme computational difficulty associated with relying on high-order numerical models, this work explores the adequacy of a generic two-degree-of-freedom lumped mass–spring model in handling this research problem. The generic model was first validated using appropriate experimental data and further utilized in evaluating crashworthiness performance under various design conditions. Statistical analysis of the system response reveals the necessary design considerations required to achieve improved crashworthiness. A multi-criteria optimization study was conducted using the resulting statistical models and suitable optimization algorithms. The optimization study suggests a set of feasible Pareto-optimal trade-off solutions that guarantee optimal crashworthiness.